The Instant and Its Shadow : A Story of Photography - Bailly, Jean-Christophe (Book collections on Project MUSE., 2020)
Via the story of two images separated by a century, Jean-Christophe Bailly's The Instant and Its Shadow is a poetic and theoretical reflection on the origins of photographic technique, the imaginative power of montage, and the relation of photography to time itself.